Maternal overweight and obesity during pregnancy: strategies to improve outcomes for women, babies, and children. Issue 4 (4th July 2022) - Dodd, Jodie M.; Deussen, Andrea R.; Mitchell, Megan; Poprzeczny, Amanda J.; Louise, Jennie
ABSTRACT: Introduction: Women with overweight and obesity, and their children, are at increased risk of adverse pregnancy, birth, and longer term health outcomes, believed to be compounded by excessive gestational weight gain (GWG). Research to date has focused on interventions to reduce excessive GWG through changes to maternal diet and/or lifestyle. Areas covered: Current clinical recommendations for GWG vary according to a woman's early pregnancy body mass index, based on assumptions that associations between GWG and adverse pregnancy outcomes are causal in nature, and modifiable. While there are small differences in GWG following pregnancy interventions, there is little evidence for clinically relevant effects on pregnancy, birth, and longer term childhood outcomes. This review considers interventional studies targeting women with overweight or obesity to reduce GWG in an effort to improve maternal and infant health, and the current evidence for interventions prior to conception. Expert opinion: GWG is not modifiable via diet and lifestyle change, and continued efforts to find the 'right' intervention for women with overweight and obesity during pregnancy are unjustified. Researchers should focus on gathering evidence for interventions prior to pregnancy to optimize maternal health and weight to improve pregnancy, birth, and longer term health outcomes associated with obesity.